2017
DOI: 10.1063/1.4974348
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of the thermal properties of single-crystalline SnSe

Abstract: The simple binary SnSe has been recently proposed as a prospective candidate for thermoelectric applications due to its exceptionally low lattice thermal conductivity. However, the thermal transport in single crystals was found to be significantly lower than in polycrystalline samples despite the presence of grain boundary scattering in the latter. In order to better understand the origin of this issue, we report here on a detailed characterization of the thermoelectric properties of a vertical-Bridgman-grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 33 publications
16
64
1
Order By: Relevance
“…These results were consistent with early studies performed on single crystal SnSe (1.9 W m -1 K -1 at 300 K perpendicular to the c-axis) [247]. Besides, the single crystal SnSe with a relative density of 99 % demonstrated that the values along the a-, b-, and c-axes were all ~1.0 W m -1 K -1 at 700 K [246], which were higher than the reported results of ~0.24, 0.34 and 0.31 along the a-, b-, and c-axes, respectively [61]. In this respect, the reported single crystal with a low calculated ρ should be at least "SnSe crystal".…”
Section: Controversy On Thermal Conductivitysupporting
confidence: 91%
See 1 more Smart Citation
“…These results were consistent with early studies performed on single crystal SnSe (1.9 W m -1 K -1 at 300 K perpendicular to the c-axis) [247]. Besides, the single crystal SnSe with a relative density of 99 % demonstrated that the values along the a-, b-, and c-axes were all ~1.0 W m -1 K -1 at 700 K [246], which were higher than the reported results of ~0.24, 0.34 and 0.31 along the a-, b-, and c-axes, respectively [61]. In this respect, the reported single crystal with a low calculated ρ should be at least "SnSe crystal".…”
Section: Controversy On Thermal Conductivitysupporting
confidence: 91%
“…At the same time, experiments based on a vertical-Bridgman-grown single crystal SnSe [246] with a high density (ρ = 6.10 ± 0.05 g cm -3 ) showed that the intrinsic κ of single crystal SnSe is likely significantly higher than that of the reported undoped SnSe single crystals with a density of ~88 % [61]. The single crystal SnSe with a relative density of 99 % showed that the κ values along the a-, b-, and c-axes were 1.2, 2.3, and 1.7 W m -1 K -1 at 300 K, respectively [246], which were higher than the values of 0.46, 0.70 and 0.67 along the a-, b-, and c-axes [61]. These results were consistent with early studies performed on single crystal SnSe (1.9 W m -1 K -1 at 300 K perpendicular to the c-axis) [247].…”
Section: Controversy On Thermal Conductivitymentioning
confidence: 98%
“…[25][26][27][28][29] Possible reasons for the unreproducible thermal conductivity data were discussed in both in detail and were related to surface oxidation, low density, large number of intrinsic defects, etc. 23,24 Based on our results, the lowest ideal strength was found along the (100) plane, which could lead to formation of cracks and hence lower the density, which may partially account for the (controversial) ultralow thermal conductivity of SnSe crystals.…”
mentioning
confidence: 80%
“…There is recent controversy regarding the intrinsic thermal conductivity in SnSe, 15,16 with a new single crystal study suggesting that j lat % 2 W m À1 K À1 within the tightly bound rocksalt layers and $1 W m À1 K À1 in the perpendicular direction (300 K values). 17 In polycrystalline samples, a range of j lat values have been reported, [18][19][20][21][22] with some suggestion that the disorder is able to reduce j lat . 21,23 The measured j lat values have also been reported to be sensitive to oxidation.…”
mentioning
confidence: 99%